Testing Of Industrial Practice Monitoring Information Systems Using The Black Box Method (Case Study: Informatics Department Of Surabaya State University) - Ronggo Alit (IJCONSIST JOURNALS, 2023)
Abstract— Industrial Practice is a means for students to understand how to gain knowledge from the web-based Industrial Practice Monitoring Information System (SEMPI), which is a system that can provide information about industrial practice programs online. This system has an advantage in terms of the speed of presentation of the resulting information. In addition, this system is web-based so that it can be accessed at any time. Measuring the quality of current software is very necessary before a software will be used by users. This aims to find out the weaknesses of the system so that the resulting data can match the data entered after the data is executed. The technique of this research is the incoming and outgoing mail information system then carried out using Black Box testing. This method focuses on data entry, system display, memory usage and speed of data execution so that if the input data does not match what is expected, the system will fail. The results of testing using this method are said to be very good because all weaknesses in the system can be identified before use. Keywords— Information systems, Industrial Practices, monitoring